2001
DOI: 10.1093/hmg/10.5.433
|View full text |Cite
|
Sign up to set email alerts
|

Mice deficient in methylenetetrahydrofolate reductase exhibit hyperhomocysteinemia and decreased methylation capacity, with neuropathology and aortic lipid deposition

Abstract: Hyperhomocysteinemia, a risk factor for cardiovascular disease, is caused by nutritional and/or genetic disruptions in homocysteine metabolism. The most common genetic cause of hyperhomocysteinemia is the 677C-->T mutation in the methylenetetrahydrofolate reductase (MTHFR) gene. This variant, with mild enzymatic deficiency, is associated with an increased risk for neural tube defects and pregnancy complications and with a decreased risk for colon cancer and leukemia. Although many studies have reported that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
471
4
7

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 560 publications
(514 citation statements)
references
References 51 publications
32
471
4
7
Order By: Relevance
“…Studies in models of folate deficiency both in vitro 84 and in vivo 85 have shown decreased DNA methylation capacity. Associations between global DNA hypomethylation in peripheral leukocytes and homozygosity for the MTHFR C677T polymorphism have also been described.…”
Section: Epigeneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in models of folate deficiency both in vitro 84 and in vivo 85 have shown decreased DNA methylation capacity. Associations between global DNA hypomethylation in peripheral leukocytes and homozygosity for the MTHFR C677T polymorphism have also been described.…”
Section: Epigeneticsmentioning
confidence: 99%
“…Knockout mouse pathogenesis CBS [137][138][139][140] Hyperhomocysteinemia Hyperkeratosis MAT1A 89 Spontaneous hepatocellular carcinoma and impaired liver regeneration MTHFR 85,141 Hyperhomocysteinemia (À/+ and À/À) Developmental retardation with cerebellar pathology (À/À) Aortic lipid deposition (À/+ and À/À) Abnormal spermatogenesis (À/À) FOLR1 (Folbp1 Embryonic lethality (À/À) mouse homolog) 90 reversed by folinic acid supplementation of (À/+) dams…”
Section: Genementioning
confidence: 99%
“…Folic acid donates methyl groups by a complex pathway where it is first converted to tetrahydrofolate (THF) by dihydrofolate reductase (DHFR) and, through a series of steps, from THF to 5-methyl-THF by N 5 N 10 -methylenetetrahydrofolate reductase (MTHFR; Chen et al, 2001). 5-methyl-THF serves to replenish the methylated form of Vitamin B12, a cofactor for methionine synthase.…”
Section: Understanding the Causes Of Ntdsmentioning
confidence: 99%
“…Methylation is essential for synthesis of membrane phospholipids, myelin basic protein, and neurotransmitters as well as for establishing proper gene expression in embryogenesis (Biniszkiewicz et al, 2002;Chen et al, 2001). During embryogenesis, all three major DNA methyltransferases (Dnmt1, Dnmt3a, and Dnmt3b) are expressed, the most important being Dnmt1 and Dnmt3b in establishing and maintaining proper genomic methylation (Fan et al, 2001;Jackson et al, 2004).…”
Section: Understanding the Causes Of Ntdsmentioning
confidence: 99%
See 1 more Smart Citation